Hubungan Radiasi Gelombang Elektromagnetik Dan Faktor Lain Dengan Keluhan Subyektif Pada Tenaga Kerja Industri Eletronik GE di Yogyakarta - Kurniawan, Bina; Wahyuni, Ida (Jurnal Promosi Kesehatan Indonesia, 2008)
Background: Work place wich use electrical energy causes electromagnetic radiation. Subjective complaint caused by electromagnetic wave radiation and the other factors like work climate, lighting, noisy. The aim of this research was to analyze electromagnetic radiation and the other factors related to employee’s subjective complaint.Method: The research that used is explanatory research, the method that used in this research is the cross sectional approach survey and statistic test that use in analyzed survey. The population consist of 144 employee of TL departement GE electronic industry. Sample based on caracteristic inclution and exclution 34 employee. The Statistic is chi square test.Result: The result of this research shows there are correlation between work climate and noise with subjective complaint. The other factors are time of work, level of radiation, and radius of radiation are not related. The lighting is not related with subjective complaint but the result of measures shows that the lighting out of range.Keywords: subjective complaint, electromagnetic wave radiation, electrical energy.